Cross-diagnostic scale-banking using rasch analysis: Developing a common reference metric for generic and health condition-specific scales in people with rheumatoid arthritis and stroke - Birgit Prodinger; Ayşe A. Küçükdeveci; Sehim Kutlay; Atilla H. Elhan; Svend Kreiner; Alan Tennant (Medical Journals Sweden, 2020)
Objectives: To develop a common reference metric of functioning, incorporating generic and health condition-specific disability instruments, and to test whether this reference metric is invariant across 2 health conditions. Design: Psychometric study using secondary data analysis. Firstly, the International Classification of Functioning, Disability and Health (ICF) Linking Rules were used to examine the concept equivalence between the World Health Organization Disability Assessment Schedule (WHODAS 2.0), Health Assessment Questionnaire (HAQ) and Functional Independence Measure (FIMTM). Secondly, a scale-bank was developed using a reference metric approach to test-equating, based on the Rasch measurement model. Participants: Secondary analysis was performed on data from 487 people; 61.4% with rheumatoid arthritis and 38.6% with stroke. Results: Three sub-domains of the WHODAS 2.0 and all items of the HAQ and FIMTM motor mapped on to the ICF chapters d4 Mobility, d5 Self-care and d6 Domestic life. Test-equating of these scales resulted in good model fit, indicating that a scale bank and associated reference metric across these 3 instruments could be created. Conclusion: This study provides a transformation table to enable direct comparisons among instruments measuring physical functioning commonly used in rheumatoid arthritis (HAQ) and stroke (FIMTM motor scale), as well as in people with disability in general (WHODAS 2.0).